2013
DOI: 10.3797/scipharm.1301-25
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Stability-Indicating RP-HPLC Method for Determination of Process Related Impurities and Degradation Droducts of Rabeprazole Sodium in Pharmaceutical Formulation

Abstract: The objective of the current study was to develop and validate a reversed-phase high-performance liquid chromatographic method for the quantitative determination of process-related impurities and degradation products of rabeprazole sodium in pharmaceutical formulation. Chromatographic separation was achieved on the Waters Symmetry Shield RP18 (250 mm × 4.6 mm) 5 μm column with a mobile phase containing a gradient mixture of solvent A (mixture of 0.025 M KH2PO4 buffer and 0.1% triethylamine in water, pH 6.4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…Stability study of RZL and ACF demonstrated satisfactory results. The type of degraded product formed, R f value and the percent drug recovery variation showed the differences from the results reported in literature for drug degradation by other analytical methods [17,[19][20] because of the nature, methodology and extent of degradation. The study activity was limited till the formation of chromatogram of degraded drug sample, its approximate interpretation, nevertheless there is a scope for the separation, quantification and analysis of the degraded products.…”
Section: Discussion and Overall Conclusioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Stability study of RZL and ACF demonstrated satisfactory results. The type of degraded product formed, R f value and the percent drug recovery variation showed the differences from the results reported in literature for drug degradation by other analytical methods [17,[19][20] because of the nature, methodology and extent of degradation. The study activity was limited till the formation of chromatogram of degraded drug sample, its approximate interpretation, nevertheless there is a scope for the separation, quantification and analysis of the degraded products.…”
Section: Discussion and Overall Conclusioncontrasting
confidence: 77%
“…Although, various analytical techniques has been developed for estimation of RZL and ACF individually or with other components in bulk drug and pharmaceutical dosage forms, the most suitable, efficient and cost effective HPTLC method has not yet been determined [15][16][17][18][19][20][21][22][23] Similarly, this technique has not been used for stability indication of drugs so far. It requires modification depending on the factors that predict the better resolution, validation within accepted limits and clear separation from degradation products.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] A few studies exist on the development of stability-indicating analytical methods for rabeprazole. 20,21 However there is no study exists on systematic forced degradation behavior of rabeprazole under stress conditions as per ICH guidelines. Hence, the purpose of the present study was to develop (a) a stability indicating assay method for rabeprazole (b) identication and characterization of all the degradation products formed under stress conditions using LC/ESI/MS/MS, accurate mass measurements and 1 H-NMR (c) proposition of degradation pathways and mechanisms and (d) in vitro toxicity evaluation of major degradation products.…”
Section: Introductionmentioning
confidence: 99%